A Research on dental caries and its epidemiology - F Mosavi (Tehran University of Medical Sciences, 1987)
In order to analyze many factors that may be effective in dental carries development, depend on the chief complaint and diagnosis clinical evaluations were performed. 357 patients seeking treatment for pain and dental infection caused by caries were selected. Different social groups were seen among the patients from high class patients like university professors, students and those who  could not afford private clinics and lower social classes who lived in poverty. Questions were asked from the patients about their hygienic status, age, respiratory health and the results were obtained. Of 357 cases who were 153 female and 204 male, 282 had dental caries while the caries rate was higher in women. 195 of average hygiene patients, 165 had caries. Of 41 god hygiene patients, 27 had caries. Caries rate in patients with mouth breathing was 48/58 ratio and those with nasal breathing 193/247. Also, among 52 cases with both oral and nasal breathing , 48 were found with dental caries.